(untitled) (Conferencea, 2024)
This article highlights the issues of developing the physical abilities of 4th-grade students through extracurricular activities. The aim of the research is to determine the effectiveness of extracurricular activities in developing physical abilities and to provide recommendations for optimizing this process, based on an analysis of scientific literature on physical education, practical observations, and the results of experimental research. Relevant recommendations for practice are given based on the research.